Reflection on epistemology and methodology in management sciences: CEDOC Case Study of “Hassan 1st University” - BAAKIR , Houssam; ELLIOUA , Hanane (Revue Internationale des Sciences de Gestion, 2025)
The epistemological position of management science is generally an essential phase in the evolution of scientific research. Its aim is to clarify the concept of knowledge that underpins a scientific approach. It is more than just a slight methodological preoccupation, since it enables us to understand the nature of the knowledge generated, how it is generated and its status. From there, it determines the purpose of the investigation, and the approaches and procedures used to carry out a scientific project. Each study unfolds and articulates a set of steps that can be repetitive and are essentially linked to the object of study. Perplexities arise from mix-ups between some of these steps. In terms of the project’s purpose, should it be considered a study designed to understand, elucidate or anticipate? Furthermore, does the approach adopted focus on the discovery or validation of hypotheses or theories? For its part, methodological choice encompasses the different procedures implemented to bring a scientific project to fruition. In this context, the scientist determines the means of data collection and processing he or she will use. This paper aims firstly to outline the major epistemological paradigms within management studies and their methodological repercussions, and secondly to carry out a study aimed at taking stock of the different epistemological paradigms and methodological choices adopted by PhD students at Hassan 1er University.